2017
DOI: 10.3389/fphys.2017.00179
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response of Visceral White Adipose Tissue of Obese Mice Exposed for 5 Days to Human Room Temperature Compared to Mouse Thermoneutrality

Abstract: Housing of laboratory mice at room temperature (22°C) might be considered a constant cold stress, which induces a thermogenic program in brown adipose tissue (BAT). However, the early adaptive response of white adipose tissue (WAT), the fat storage organ of the body, to a change from thermoneutrality to room temperature is not known. This was investigated here for various WAT depots, focusing on epididymal WAT (eWAT), widely used as reference depot. Male adult diet-induced obese (DIO) C57BL/6JOlaHsd mice house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Previous studies have also shown that thermoneutrality increases BAT mass in obesity‐resistant strain A/J male mice fed a HF diet (60% kcal fat) giving rise to a pale color, indicating that increased environmental temperature triggers BAT whitening . In line with these studies, several studies have reported increased adiposity in HF‐fed mice at thermoneutral conditions, while others did not . In respect to human studies, combination of HF diet with high indoor temperature, often used in developed countries, especially in winter, may be important factors that contribute to obesity .…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have also shown that thermoneutrality increases BAT mass in obesity‐resistant strain A/J male mice fed a HF diet (60% kcal fat) giving rise to a pale color, indicating that increased environmental temperature triggers BAT whitening . In line with these studies, several studies have reported increased adiposity in HF‐fed mice at thermoneutral conditions, while others did not . In respect to human studies, combination of HF diet with high indoor temperature, often used in developed countries, especially in winter, may be important factors that contribute to obesity .…”
Section: Discussionmentioning
confidence: 66%
“…We have previously published 24 h metabolism profiles for mice using low resolution respirometry in their home cages with bedding, drink, and food, at both 22 °C and 29 °C [19]. Using the lowest average over 3 consecutive readings to represent RMR (equivalent to 24 min), these data showed that at 29 °C, the ratio for DEE 29 /RMR 29 was 1.38, while at 22 °C, the ratio DEE 22 /RMR 29 was 2.10, similar to the ratios derived here.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological mechanisms through which housing temperature influences bone metabolism and homeostasis in mice have not been established, but based on precedent (19) likely involve neuroendocrine pathways related to activation of adaptive thermogenesis, particularly non-shivering thermogenesis. As noted in the Introduction, mice are facultative daily heterotherms and experience fasting-induced reductions in body temperature when subjected to housing temperatures below their thermoneutral zones (20).…”
Section: Discussionmentioning
confidence: 99%